Biocontrol of post-harvest green mould rot (Penicillium digitatum) of kinnow fruits using microbial antagonists - and R.B. GAUR, R.N. SHARMA*, R.P. MAHARSHI1 (Indian Phytopathology, 2012)
Kinnow (Citrus deliciosa) fruits are prone to attack by several microorganisms during storage and marketing. Green mould rot caused by Penicillium digitatum is one of the most prominent post-harvest rots of kinnow fruits. Twelve native and exotic strains of fungal [Trichoderma hamatum (HP-20), T. harzianum (TG-1), T. viride-1, T. viride-2, Gliocladium deliquescens, G. virens and Chaetomium globosum (HP-29)], yeasts [Debaryomyces hansenii, Sporidiobolus pararoseus (KFY-1)] and bacterial [Bacillus subtilis, Pseudomonas fluorescens (CHAO), P. fluorescens (Pf-1)] antagonists were evaluated against the P. digitaum. Debaryomyces hansenii and S. pararoseus (KFY-1) proved superior over rest of the antagonists tested against pathogen by inhibiting 89.63 and 83.15 per cent mycelial growth respectively. Pseudomonas fluorescens (Pf-1), B. subtilis and P. fluorescens (CHAO) exhibited 82.41, 74.44 and 69.82 per cent growth inhibition, respectively. Maximum reduction in rot incidence was observed in fruits treated with spore suspension (109 cfu/ml) of D. hansenii and S. pararoseus (KFY-1) where, 87.75 and 79.99 per cent in pre-inoculation and 82.60 and 73.33 per cent in post-inoculation treatment was noted, respectively. Spore suspension (109 cfu/ml) of P. fluorescens (Pf-1) and B. subtilis were found to be the next in order of bioefficacy against the fruit rotting, protecting the treated fruits.